Impact of physical exercise programs in breast cancer survivors on health-related quality of life, physical fitness, and body composition: Evidence from systematic reviews and meta-analyses - Joaquim, Ana; Leão, Inês; Antunes, Pedro; Capela, Andreia; Viamonte, Sofia; Alves, Alberto J.; Helguero, Luísa A.; Macedo, Ana (Frontiers in Oncology, 2022)
Background: Breast cancer is the most common cancer worldwide, and despite remarkable progress in its treatment, the survivors' quality of life is hampered by treatment-related side effects that impair psychosocial and physiological outcomes. Several studies have established the benefits of physical exercise in breast cancer survivors in recent years. Physical exercise reduces the impact of treatment-related adverse events to promote a better quality of life and functional outcomes. Aim: This study aims to provide an overview of systematic reviews and meta-analyses on the effect of physical exercise on the health-related quality of life, cardiorespiratory fitness, muscle strength, and body composition of breast cancer survivors. Methods: PubMed and Cochrane databases were searched for systematic reviews and meta-analyses from January 2010 to October 2022. The main focus was ascertaining the effectiveness of physical exercise in breast cancer survivors undergoing curative treatment (surgery and/or radiotherapy and/or chemotherapy). Two reviewers independently screened the literature, extracted the data, and assessed the risk of bias in the included studies. Results: A total of 101 studies were identified, and 12 were yielded for final analysis. The eligible studies included nine systematic reviews/meta-analyses, one meta-analysis/meta-regression, and two systematic reviews. The number of randomised clinical trials included in each review varied from 11 to 63, and the number of participants was from 214 to 5761. A positive and significant effect of different physical exercise interventions on health-related quality of life was reported in 83.3% (10 studies) of the eligible studies. Physical exercise also improved cardiorespiratory fitness (3 studies; 25%) and showed to be effective in reducing body weight (3 studies; 25%) and waist circumference (4 studies; 33.3%). Conclusions: Our results suggest that physical exercise is an effective strategy that positively affects breast cancer survivors' quality of life, cardiorespiratory fitness, and body composition. Healthcare professionals should foster the adoption of physical exercise interventions to achieve better health outcomes following breast cancer treatments. Systematic Review Registration: INPLASY identifier INPLASY2022110053 and DOI number 10.37766/inplasy2022.11.0053.